Agglomeration tendency of a fluidized bed during addition of different phosphate compounds. (15th May 2020) - Sevonius, Christoffer; Yrjas, Patrik; Lindberg, Daniel; Hupa, Leena
Abstract: Phosphorus has been observed to cause agglomeration during fluidized bed combustion of phosphorus-rich biomass. Phosphorus can react with alkali during combustion, forming low melting phosphates that glue the bed particles together, or form phosphates that react with the bed material. In this work, seven different phosphate compounds (KH2 PO4, NaH2 PO4, CaHPO4, NH4 H2 PO4, K3 PO4, Na3 PO4, Ca3 (PO4 )2 ) were tested. Experiments were performed in an electrically heated laboratory-scale fluidized bed reactor at 750, 800, 850 and 900 °C and the feeding of the phosphates continued until defluidization occurred or until 10 g of a phosphate-compound had been added. Defluidization was detected by a sudden decrease in the pressure drop over the bed and a simultaneous increase in the temperature difference between the upper and lower bed. Samples of the bed material were taken after each test and cast in epoxy, ground and polished to get a cross-section and then analyzed with SEM/EDX. KH2 PO4, NaH2 PO4, and NH4 H2 PO4 were found to cause defluidization by melt formation whereas K3 PO4 and Na3 PO4 caused defluidization via reaction with the quartz bed material forming alkali silicate.